Temperature Effects,Frieden-Hawkins´Order-Measure, and Wehrl Entropy - Pennini, Flavia Catalina (2012)
We revisit the Frieden-Hawkins' Fisher order measure with a consideration of temperature effects. To this end, we appeal to the semiclassical approach. The order-measure's appropriateness is validated in the semiclassical realm with regard to two physical systems. Insight is thereby gained with respect to the relationships amongst semiclassical quantifiers. In particular, it is seen that Wehrl's entropy is as good a disorder indicator as the Frieden-Hawkins' one. © 2012 by the authors; licensee MDPI, Basel, Switzerland.